EFFICIENT PUBLIC FINANCIAL MANAGEMENT FOR EFFECTIVE GOVERNANCE AND SUSTAINABLE URBAN DEVELOPMENT - Musau, Salome (Journal of Public Policy and Administration, 2022)
Purpose: This paper looked at the principles of good financial governance that including: Financial planning practices, Revenue mobilization strategies, monitoring and evaluation units and assessed how they affect sustainable urban development. Methodology: Through a situational analysis, this report comes up with a conceptual literature which evaluates existence of correlation between efficient governance, monetary management as well as sustainable urban development. Findings: The paper established that the fundamental reason for public financial management is logical, efficient and time-time evaluation of financial practices employed by the urban councils to promote institutional learning on one hand as well as improving future performance and therefore, enhance the standard of their financial decision making. And thus, it concludes that effective and efficient use of public funds depends on the level of Accountability. Also, good financial governance and good institutional structures are crucial in attaining sustainable development. Unique Contribution to Theory, Practice and Policy: The paper recommends that, public institutions should strive to attain good financial governance which enhances management decisions, accountability and organization learning in attaining sustainable development. This paper also recommends that M&E should support evidence-based decision making as well as nominal compliance. In order to enhance planning, service delivery and policy process M&E should be properly institutionalized, funded and located.